2018
DOI: 10.1002/jcb.27600
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐targeted microbubble enhances migration and therapeutic efficacy of marrow mesenchymal stem cell on rat middle cerebral artery occlusion stroke model

Abstract: To investigate the role of ultrasound-targeted microbubbles in the homing effect of bone marrow-derived mesenchymal stem cells (BMSCs) and in the therapeutic efficacy of BMSCs on the ischemic stroke. A middle cerebral artery occlusion (MCAO) model was induced by plug wire preparation. Seventy-two hours after MCAO, the treatment of BMSCs with ultrasound-targeted microbubble was assessed via modified neurological severity score (mNSS), infarct volumes, and cerebral edema. In addition, immunofluorescence was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…UTMd is combined with BMSc transplantation, there is a beneficial effect on the engraftment of cells (52,53). Ultrasound microbubbles can enhance the therapeutic effect of BMScs in diseases and promote BMSc homing (51,54,55). In the present study, the BUTMd + siRNA Nc group had an intermediate therapeutic effect.…”
Section: Discussionmentioning
confidence: 45%
“…UTMd is combined with BMSc transplantation, there is a beneficial effect on the engraftment of cells (52,53). Ultrasound microbubbles can enhance the therapeutic effect of BMScs in diseases and promote BMSc homing (51,54,55). In the present study, the BUTMd + siRNA Nc group had an intermediate therapeutic effect.…”
Section: Discussionmentioning
confidence: 45%
“…BMSCs cells were made to express GFP protein which was expressed higher in the USSM group. This indicates that ultrasound-targeted microbubbles reduce cerebral edema and cerebral infarction volume, enhance the homing effect of vein transplanted BMSCs, improve the neurological function score, and thus enhance the effect of stem cell transplantation treating ischemic stroke …”
Section: Applications Of Ultrasound In Stem Cells Engineering and Reg...mentioning
confidence: 92%
“…This indicates that ultrasound-targeted microbubbles reduce cerebral edema and cerebral infarction volume, enhance the homing effect of vein transplanted BMSCs, improve the neurological function score, and thus enhance the effect of stem cell transplantation treating ischemic stroke. 134 An acousto-fluidic mediated approach was used to deliver plasmids in the human hematopoietic stem cells and progenitor cells. This method enabled pore formation and permeabilization of cell membranes under the effect of acoustic waves.…”
Section: Applications Of Ultrasound In Stem Cellsmentioning
confidence: 99%
“…Ultrasound-targeted microbubble destruction can disrupt biological barriers and increase vascular permeability, including the blood-brain barrier (BBB) [ 45 ]; this technique may help more transplanted cells to migrate to the injured brain area. Qian et al found that ultrasound-targeted microbubbles enhanced the homing effect of BMSCs during the application of transplantation to treat ischemic stroke [ 46 ]. This improved level of homing led to the amelioration of cerebral edema, a reduction in infarct size, and an improved neurological function score in a rat model of MCAO.…”
Section: Physical Approaches To Improve the Efficiency Of Msc Transplantationmentioning
confidence: 99%